2017
DOI: 10.1123/jsm.2016-0101
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interorganizational Relationships on Elite Athlete Development Processes

Abstract: Previous studies acknowledge the importance of sporting organizations’ developing partnerships with clubs for athlete development purposes. However, there are no studies that address the way partnerships influence athlete progression and pathways. This study explores interorganizational relationships (IORs) between a tennis federation and tennis clubs in their efforts to improve player development processes. Document analysis and semistructured interviews with representatives from clubs and the Flemish federat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
47
6
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 39 publications
8
47
6
1
Order By: Relevance
“…Sponsorship is reaching its limits, political subsidies are what they are, so we cannot hope to multiply by ten our financial income so we need to deal with our shoestring means available, with what we have but (…) we also try to use exchanges and contacts. Federation 5Contrary to the resource dependence perspective often mobilised to examine NPO collaboration for service delivery (Gazley & Brudney, 2007;Sowa, 2009;Sotiriadou et al, 2017), NPOs do not collaborate for socially responsible programs to exert power and control over organizations with scarce resources (Barringer & Harrisson, 2000). As Sowa (2009) noted, NPOs first seek their basic programmatic needs before seeking to implement complementary projects.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sponsorship is reaching its limits, political subsidies are what they are, so we cannot hope to multiply by ten our financial income so we need to deal with our shoestring means available, with what we have but (…) we also try to use exchanges and contacts. Federation 5Contrary to the resource dependence perspective often mobilised to examine NPO collaboration for service delivery (Gazley & Brudney, 2007;Sowa, 2009;Sotiriadou et al, 2017), NPOs do not collaborate for socially responsible programs to exert power and control over organizations with scarce resources (Barringer & Harrisson, 2000). As Sowa (2009) noted, NPOs first seek their basic programmatic needs before seeking to implement complementary projects.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Earlier studies (Sowa, 2009;Sotiriadou et al, 2017) suggest that the motivations for nonprofit F o r P e e r R e v i e w 11 collaboration could be influenced by the nature of the service delivered. Accordingly, the motivations to collaborate for socially responsible programs could differ from other collaboration forms because the creation of positive social change (Aguilera et al, 2007) underpins these collaborations.…”
Section: Motives For Nonprofit Collaboration For Socially Responsiblementioning
confidence: 99%
“…Within sport management literature, few studies have sought to unfold interorganizational relationships. Sotiriadou, Brouwers, De Bosscher, and Cuskelly (2017) found that a good collaboration between a club and a sport federation enhanced the elite sport pathways. The federation offered resources and consultancy and as a result, the local clubs enhanced the quality of their training environments and coach education.…”
mentioning
confidence: 99%
“…This collaboration was successful because the clubs improved their player development programs and their coaches gained more knowledge and expertise. However, they emphasized the importance of the context (e.g., organizational, national and sport context) on inter-organizational relationships and therefore they called for more examples of and knowledge within inter-organizational relationships in sport (Sotiriadou et al, 2017). In talent development, sport psychology researchers have mainly taken an individual perspective (e.g., individual training histories; Araujo & Davids, 2009), and looked at the role of coaches, parents or peers in young athletes' environments (e.g., Martindale, Collins, & Abraham, 2007) with little attention given to how different agents and organizations interact to facilitate talent development (Fletcher & Wagstaff, 2009).…”
mentioning
confidence: 99%
“…Robinson & Minikin, 2011;Truyens, De Bosscher, & Sotiriadou, 2016), organisational theory, inter-organisational relationships or stakeholder involvement theories (e.g. Sotiriadou, Brouwers, De Bosscher, & Cuskelly, 2017;Thibault, Kihl, & Babiak, 2010), (elite) sport policy (e.g. see list above), culture (e.g.…”
Section: Defining Hp Sport and Its Unique Characteristicsmentioning
confidence: 99%